AN INTERPERSONAL MEANING ANALYSIS OF THE SECOND-GRADE STUDENTS’ NARRATIVE TEXTS - Nurinayah Nurinayah (Universitas Galuh, 2021)
This paper identified the language use in the second-grade students’ narrative texts to create the interaction between the students and their stories. Furthermore, the language use as the interaction was called interpersonal meaning (mood and residue). Moreover, the focus of the study was on identifying the use of interpersonal meaning (mood and residue) as the engagement between the students and their stories in writing contexts and the realization of mood types which cover statements, offers, questions, and commands in narrative texts. Therefore, the study was aimed at figuring out (1) the realization of interpersonal meaning through mood and residue and (2) the most dominant mood types realized on the second-grade students’ narrative texts. In this study, descriptive qualitative method was employed to analyze and interpret the data by using words. The findings showed that (1) the use of mood and residue was identified as the realization of interpersonal meaning which completed the language features of narrative texts and (2) the most dominant mood type was statements which the students used to express and share their feeling in order to create the engagement between them and their story, the stories and the readers. In brief, the use of language in creating the interaction in narrative texts could be expressed by exploring interpersonal meaning (mood and residue) and choosing mood types that appropriate to share the feeling. Thus, this study provided some suggestions for the teachers/lecturers and the students which they should explore the use of language to interact in writing context by applying interpersonal meaning which covered mood types to get involved and engaged in the story. Keywords: Interpersonal meaning, mood, residue, second grade, narrative texts